Reviewing Michael Scriven's Contributions to JMDE - Michael J. Hart; Michael A. Harnar (The Evaluation Center at Western Michigan University, 2024)
Dr. Michael Scriven was a founding member and editor of JMDE, as well as a prolific contributor. This manuscript reviews Scriven's substantive manuscripts and revisits the three most-downloaded articles.